2015
DOI: 10.1021/acs.est.5b01614
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Life Cycle Analysis of In Vitro Biomass Cultivation for Cultured Meat Production in the United States

Abstract: Cultured, or in vitro, meat consists of edible biomass grown from animal stem cells in a factory, or carnery. In the coming decades, in vitro biomass cultivation could enable the production of meat without the need to raise livestock. Using an anticipatory life cycle analysis framework, the study described herein examines the environmental implications of this emerging technology and compares the results with published impacts of beef, pork, poultry, and another speculative analysis of cultured biomass. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
201
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(233 citation statements)
references
References 29 publications
5
201
1
9
Order By: Relevance
“…Although with large uncertainty ranges, life cycle analyses indicate that the overall environmental impacts of cultured meat production could be lower than those of most conventionally produced meat (Tuomisto and Teixeira de Mattos 2011;Mattick et al 2015). However, a great deal of research is still needed to establish an industrial-scale culturing system (Fayaz Bhat and Fayaz 2011).…”
Section: Alternative Protein Sourcesmentioning
confidence: 99%
“…Although with large uncertainty ranges, life cycle analyses indicate that the overall environmental impacts of cultured meat production could be lower than those of most conventionally produced meat (Tuomisto and Teixeira de Mattos 2011;Mattick et al 2015). However, a great deal of research is still needed to establish an industrial-scale culturing system (Fayaz Bhat and Fayaz 2011).…”
Section: Alternative Protein Sourcesmentioning
confidence: 99%
“…After estimating the potential environmental impacts of large-scale cultured meat production compared with conventionally produced European meat products, Tuomisto and Teixeira de Mattos (2011) reported that artificial meat used 82 to 96% less water. According to Mattick et al (2015), although artificial meat could require less land and agricultural inputs than livestock products, energy use would be more intensive due to the replacement of biological functions with industrial equivalents. Even so, the consumer acceptance of cultured meat products remains unknown and as a result such production is unlikely to be marketable in the near future (Hocquette, 2016).…”
Section: Overview Of Strategies To Reduce the Water Use Of Ruminant Pmentioning
confidence: 99%
“…In vitro meat production has to date supplanted a bovine, ovine or porcine body with a technological one, as serum supply systems supplant blood vessels and sterile laboratory conditions supplant white blood cells. As Mattick et al (2015a) comment, what was previously the result of 'internal biological functions (temperature regulation, digestion, oxygenation, nutrient distribution, disease prevention, etc. ) fueled by agricultural energy inputs (feed)' (p. 11946) must thus be performed by industrial energy.…”
Section: Relative Silences In Promissory Depictionsmentioning
confidence: 99%